2013
DOI: 10.1097/opx.0000000000000073
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Shapes of Chinese Emmetropes and Myopic Astigmats Aged 10 to 45 Years

Abstract: Corneal shapes were influenced by age and MA in the Hong Kong Chinese. These results highlight the importance of controlling these factors when designing a study on corneal shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…33 To investigate the effect of age and refractive errors on regional corneal shapes, we compared the semimeridian corneal shape factors (nasal, temporal, superior, and inferior quadrants) between the myopic astigmats and emmetropes collected from three age cohorts (10 to 15, 20 to 25, and 40 to 45 years). 27 Our results indicated that the myopic astigmats exhibited a more prolate temporal corneal shape than the emmetopes in all the three age cohorts studied, and the higher degree of WTR astigmatism was found to be associated with more prolate in temporal and nasal corneal shape. However, because nearly all of the myopic astigmats had WTR astigmatism (44 of 47)Van astigmatic subtype typically found in younger populations 2,34,35 V whether myopic astigmats with ATR astigmatism also exhibit similar changes in the corneal shape remains unclear.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…33 To investigate the effect of age and refractive errors on regional corneal shapes, we compared the semimeridian corneal shape factors (nasal, temporal, superior, and inferior quadrants) between the myopic astigmats and emmetropes collected from three age cohorts (10 to 15, 20 to 25, and 40 to 45 years). 27 Our results indicated that the myopic astigmats exhibited a more prolate temporal corneal shape than the emmetopes in all the three age cohorts studied, and the higher degree of WTR astigmatism was found to be associated with more prolate in temporal and nasal corneal shape. However, because nearly all of the myopic astigmats had WTR astigmatism (44 of 47)Van astigmatic subtype typically found in younger populations 2,34,35 V whether myopic astigmats with ATR astigmatism also exhibit similar changes in the corneal shape remains unclear.…”
mentioning
confidence: 57%
“…27 These two studies shared similar methodology with key differences in the recruitment of the nonastigmatic group (current, simple myopes; previous, emmetropes) and the criteria for visual acuity (current, logMAR [logarithm of the minimum angle of resolution] 0.10; previous, logMAR 0.00) and myopia (current, M e j0.50 D; previous, M e j1.00 D). Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leung and coworkers 26 made Pentacam measurements on 100 Chinese subjects across a range of ages with either compound myopic astigmatism or emmetropia. Corneas became less prolate with age in both refractive error groups.…”
Section: Peripheral Defocus and Myopia Controlmentioning
confidence: 99%